Aplikasi Augmented Reality sebagai Media Edukasi Monumen Bersejarah di Indonesia - Dheni Septian Nurachman; Eka Wahyu Hidayat; Euis Nur Fitriani Dewi (Jurnal Teknologi Informasi dan Multimedia, 2024)
Indonesia has many monuments spread from Sabang to Merauke, because of the many historical events. So, to be able to explore the historical monuments spread across Indonesia, can only be done by visiting the region, so not all levels of people can easily visit all regions of Indonesia. Based on these problems, an application was created which aims to be an educational medium for introducing historical monuments in Indonesia using Augmented Reality technology. By utilizing Augmented Reality as an interactive educational medium, it is hoped that it can increase interest in learning from many groups by using smartphones to introduce historical monuments in Indonesia and obtain information and visualization with 3D objects. The research method that will be used in this research has four stages including data collection, application design and application creation, evaluation and conclusions. Application design uses Augmented Reality technology with the MDLC (Multi-media Development Life Cycle) approach method. Based on the results of Black Box testing, all functional systems in the application can function properly. The final results of the evaluation using the System Usability Scale (SUS) testing method with 30 respondents received a score of 77.166. So, it can be concluded from this assessment that the Augmented Reality application as an educational medium for historical monuments in Indonesia in the adjective rating category is GOOD with a grade scale of C, which means usability based on the data obtained has received an acceptable level of acceptance. So this application can be said to be suitable for use.